GBA and JOSS for Enhancing Students’ Writing Proficiency - Dwi Hastuti; Setia Rini (Scripta : English Department Journal, 2023)
This research was conducted to examine whether Genre Based Approach can improve students' descriptive text writing skills. A quantitative research design was adopted in this study using a pre-test and post-test control design. The research sample was 70 students of grade X Mechatronics of SMKN 3 Salatiga. The instrument is a written test. Data were analyzed using SPSS. The results showed that the average value of the pre-test was 65.56 (SD = 9.92672) and the average value of the post-test was 77.69 (SD = 6.56754). Based on the t-test, the sig. is 0.00. It is less than 0.05, so that there is a significant difference before and after the treatment. study of Genre-based Approach had a positive effect on students' writing skills in descriptive text. The study provides valuable insights and contributes to the broader field of research on the relationship between Genre-Based Approach, Jigsaw Online Searching Strategy and students’ writing proficiency.